Toilet Water Management in Bedengan Tourism Park Malang Using LoRa-Based Wireless Sensor Network - Soelistianto, Farida Arinie; Koesmarijanto, Koesmarijanto; Putra, Sendy Egiana Wika (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
The availability of adequate public facilities at Bedengan Tourism Park, Malang, is essential, particularly toilet facilities that require a reliable water supply. Currently, toilet water distribution is channeled through a single main pipe divided into several outlets, resulting in limited water flow due to small pipe dimensions and the absence of a water storage reservoir. These conditions cause insufficient water availability, especially during peak usage. To address this issue, this study designs and implements a toilet water distribution system using a wireless sensor network integrated with solar energy. The proposed system utilizes an ESP32 microcontroller, HC-SR04 ultrasonic sensor, YF-S201 water flow sensor, and a LoRa E220-900T22D module for long-range communication. Experimental results show that the HC-SR04 sensor achieves an accuracy of 99.951%, while the YF-S201 water flow sensor reaches an accuracy of 97.943%. The maximum LoRa transmission distance achieved is 560 meters. Solar charging for 6 hours fully charges a 100 Ah battery, while the discharge rate is 0.236 Ah, allowing the system to operate for up to 423 hours. Quality of Service evaluation indicates a throughput of 82.5%, packet loss of 0.996%, and an average delay of 0.585 seconds. The system enables both automatic and manual pump control via a website and provides real-time monitoring of water volume and reservoir level.